Occurrence of Shiga-toxigenic Escherichia coli in Stomoxys calcitrans (Diptera: Muscidae) - de Castro,Bruno Gomes (2013)
This study aimed to verify the occurrence of Shiga toxin-producingEscherichia coli (STEC) strains in three distinct anatomic parts of the stable fly Stomoxys calcitrans by multiplex polymerase chain reaction (PCR Multiplex). According to the results obtained,E. coli was identified in 19.5% of the stable flies. Shiga toxin genes were detected in 13% of the E. coli isolated, most frequently from the surface, followed by abdominal digestive tract and mouth apparatus of insects, respectively. This is the first study to detect presence of STEC in Stomoxys calcitrans in Brazil; it has also revealed the potential role of stable flies as carriers of pathogenic bacterial agents.